For the love of God and people : a philosophy of Jewish law - Dorff, Elliot N. (UPCC book collections on Project MUSE., 2007)
"Every generation of Jews in every denomination of Judaism finds itself facing complex legal issues. The status of same-sex unions and stem-cell research are just two of a myriad of thorny questions Jewish legal experts grapple with today. How do the rabbis who draft responses to these questions reach their conclusions? What informs their decisions and their approach to Jewish law?" "Acclaimed writer and legal scholar Elliot Dorff addresses these and other questions in this intelligent, accessible guide to the philosophy that shapes Jewish law. What motivates modern Jews to follow Jewish law? How does Jewish law strike the balance between continuity and change? On what grounds and under what circumstances do human beings have the authority to interpret or even change God's laws?"--Jacket.